Characterization of adsorption mode of new B2 bradykinin receptor antagonists onto colloidal Ag substrate. (10th January 2013) - Sobolewski, Dariusz; Proniewicz, Edyta; Skołuba, Dominika; Prahl, Adam; Ozaki, Yukihiro; Kim, Younkyoo; Proniewicz, Leonard M.
Abstract : In this paper, the surface‐enhanced Raman scattering (SERS) spectra of the potent B2 bradykinin receptor antagonists, [D‐Arg 0, Hyp 3, Thi 5, 8, L‐Pip 7 ]BK, Aaa[D‐Arg 0, Hyp 3, Thi 5, 8, L‐Pip 7 ]BK, [D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK, and Aaa[D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK, were measured when immobilized onto a colloidal assembly of apparently randomly adhering Ag spheres with diameters of approximately 20 – 25 nm. The observed SERS bands corresponding to different vibrational modes of the molecule, attached to or near Ag, and the variations in these bands resulting from competitive interactions of the functional groups of the peptides with the SERS‐active Ag surfaces were analyzed in this study. Briefly, it was shown that Pip, in generally in vertical orientation, and Thi, in the edge‐on position, relative to the colloidal Ag surface interacted with this surface through their lone electron pairs on the nitrogen and sulfur atoms, respectively. The imide bond of the X‐Pro peptide linkage and the guanidine group of Arg were involved in the adsorption process. In addition, it was demonstrated that the specific differences in the amino acid sequences slightly influenced the mode of adsorption. For example, Aaa in Aaa[D‐Arg 0, Hyp 3, Thi 5, 8, L‐Pip 7 ]BK and Aaa[D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK and D‐Phe (vertical with respect to the colloidal Ag surface) in [D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK, and Aaa[D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK assisted in the adsorption of these peptides onto the colloidal Ag particles. To discuss these spectral alterations due to the different surface adsorption mechanisms of these peptides, the spectral changes were analyzed according to the adsorption process and Fourier‐transform‐Raman spectra. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this study, we discussed the orientation and mode of adsorption of [D‐Arg 0, Hyp 3, Thi 5, 8, L‐Pip 7 ]BK, Aaa[D‐Arg 0, Hyp 3, Thi 5, 8, L‐Pip 7 ] BK, [D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK, and Aaa[D‐Arg 0, Hyp 3, Thi 5, D‐Phe 7, L‐Pip 8 ]BK, potent B2 bradykinin receptor antagonists, adsorbed on a colloidal Ag surface, using SERS. To reveal the adsorption mechanism of these species from their SERS spectra, Fourier‐transform‐Raman spectra of the non‐adsorbed molecules were measured and then compared with corresponding SERS spectra.